Further evidence for two metamorphical events in the Mawson Continent. Issue 1 (4th December 2017) - Williams, Megan A.; Kelsey, David E.; Hand, Martin; Raimondo, Tom; Morrissey, Laura J.; Tucker, Naomi M.; Dutch, Rian A.
Abstract: In this study, in situ and erratic samples from George V Coast (East Antarctica) and southern Eyre Peninsula (Australia) have been used to characterize the microstructural, pressure–temperature and geochronological record of upper amphibolite and granulite facies polymetamorphism in the Mawson Continent to provide insight into the spatial distribution of reworking and the subice geology of the Mawson Continent. Monazite U-Pb data shows that in situ samples from the George V Coast record exclusively 2450–2400 Ma ages, whereas most erratic samples from glacial moraines at Cape Denison and the Red Banks Charnockite record only 1720–1690 Ma ages, consistent with known ages of the Sleaford and Kimban events, respectively. Phase equilibria forward modelling reveals considerable overlap of the thermal character of these two events. Samples with unimodal 1720–1690 Ma Kimban ages reflect either formation after the Sleaford event or complete metamorphical overprinting. Rocks recording only 2450–2400 Ma ages were unaffected by the younger Kimban event, perhaps as a result of unreactive rock compositions inherited from the Sleaford event. Our results suggest the subice geology of the Mawson Continent is a pre-Sleaford-aged terrane with a cover sequence reworked during the Kimban event.